The Role of Environmental Accounting in Social Responsibility with the Classical and Contemporary Maqashid Sharia Approach - Tantina Haryati (Future Science, 2021)
The role of environmental accounting is reflected in all activities related to its social responsibility to the environment. Universities are mirrors and printers of the younger generation that produce dignified and well-behaved people in managing their environment. The classical Islamic perspective states that environmental social responsibility is by the concept of fiqh al-biah. While the contemporary Islamic perspective refers to the concept of Jasser Auda, namely Hifdz al-huquq al Insan. This research uses qualitative research with phenomenology approach. The object of this research is the role of environmental accounting in social responsibility with a classical and contemporary maqashid sharia approach. The objectives of this study are 1) To obtain empirical evidence of the role of environmental accounting in social responsibility with a classical maqashid sharia approach. 2) To obtain empirical evidence of the role of environmental accounting in social responsibility with a contemporary maqashid sharia approach. The results of this study indicate that 1) Environmental accounting plays an active role in social responsibility with a classical Islamic perspective, namely maqashid sharia: fiqh al-biah. 2) Contemporary views indicate a stronger role in the implementation of environmental management, especially in the hifdz al-huquq al-Insan approach (human rights protection).